Stochastic refinement systems and nonseparable random geometric structures - Virchenko, Yu.P.; Shpilinskaya, O.L. (Вопросы атомной науки и техники, 2001)
Probabilistic study method of fractally disodered media is proposed. It is suggested on the base of introducing of the space refinement concept.